Predictive accuracy of RSA migration thresholds for cemented total hip arthroplasty stem designs. Issue 4 (July 2018) - Teeter, Matthew G; McCalden, Richard W; Yuan, Xunhua; MacDonald, Steven J; Naudie, Douglas D
Introduction: Radiostereometric analysis (RSA) migration thresholds for cemented total hip stems have been established beyond which an unacceptably high risk of revision is likely to occur. These thresholds are subsidence >0.23 mm or >1.2 mm after 2 years. The purpose of this study was to retrospectively examine after long-term follow-up the predictive accuracy of the two thresholds. Methods: Data from two previous prospective RSA trials with 2 year follow-up for which minimum 10 year survivorship data was available were used. Thirty-six patients received a Spectron stem, 17 patients received an Exeter stem, and 17 patients received a CPCS stem. Subsidence after 2 years was compared to the migration thresholds, and long-term survivorship and clinical outcome scores were obtained. Results: At 2 years, the Spectron stem subsided 0.046 ± 0.160 mm, the Exeter stem subsided 1.218 ± 0.320 mm, and the CPCS stem subsided 0.681 ± 0.246 mm ( p < 0.0001). The Spectron stem passed both thresholds, the Exeter stem failed both thresholds, and the CPCS stem passed 1 and failed 1 threshold. At 10 years, survivorship exceeded 90% for all stems. Conclusion: All stems demonstrated strong 10 year survivorship and equivalent clinical outcome scores, but this success would not have been equally predicted across RSA migration thresholds. Although RSA is a useful predictive tool, care should be taken in applying migration thresholds only to those stem designs they are indicated for, with the threshold of 1.2 mm of subsidence at 2 years being most broadly applicable.